The Effect of Functional Training on The Central Strength of The Muscles of The Hitting Hand Arm and The Digital Level of The Volleyball Aces Skill - Ibrahim, Enam (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The first chapter included the introduction and the importance of the research through the functional efficiency, the level of central strength and physical training methods through the latest methods to achieve training achievements, while the second chapter included the researcher’s use of the experimental method with the experimental and control groups system to suit the nature of the research, while the research sample was selected by the random method and consisted of (20) players of the Karkh Volleyball Club for the season 2023-2024, The third chapter included the presentation and discussion of the results of the pre and post tests of the research sample in the two variables (back muscles and legs) and providing a database of the arithmetic averages of the strength of the stabilizing muscles of the body and the skill of the aces in volleyball as an indicator for comparison and legalization of training loads for volleyball players, as for the fourth chapter, the researcher concluded that the arithmetic averages of back muscle strength reached (82. (77) where the percentage of improvement reached (12.01%) in favor of the post-measurement and this confirms its importance, and the arithmetic means of the strength of the leg muscles reached (7.33) where the percentage of improvement reached (14.78%) in favor of the post-measurement and this confirms its importance and recommended the use of databases for the arithmetic means of body-stabilized muscle strength tests as an indicator of ground training processes and comparison with abducted age groups, as well as the importance of the ability of volleyball players to perform body-stabilized muscle strength tests and ground training for the participating muscles.